2003
DOI: 10.2519/jospt.2003.33.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Fabella Syndrome with Manual Therapy: A Case Report

Abstract: Study design: Clinical case report. Objectives: To educate clinicians about fabella syndrome as a possible cause for posterolateral knee pain and dysfunction. Also to describe a physical therapy intervention strategy for posterolateral knee pain secondary to hypomobility or malposition of a fabella. Background: A 44-year-old, physically fit, Caucasian male with a 10-year history of left posterolateral knee pain and functional limitations during athletic activities, walking, and activities of daily living prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 11 publications
2
27
0
1
Order By: Relevance
“…A literature review revealed ten publications describing fabella syndrome [8, 9, 13, 14, 16-20]. All publications were evidence level IV, with six case reports and four case series, the largest of which described 16 patients [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A literature review revealed ten publications describing fabella syndrome [8, 9, 13, 14, 16-20]. All publications were evidence level IV, with six case reports and four case series, the largest of which described 16 patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment with physiotherapy was found to be successful in a minority of cases. Zipple et al describe in detail the technique of manual mobilisation of the fabella to achieve pain relief [13]. The largest case series described five out of sixteen patients (31%) responding to conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8 Because the fabella is an intra-articular structure with a cartilage lining, this can also degenerate and lead to chronic pain and localized arthritis. Physical examination may reveal the presence of swelling/tenderness in the posterolateral aspect of the knee.…”
Section: Discussionmentioning
confidence: 99%
“…6,9 Patel et al 9 presented the case of a 67-yearold man with symptoms of pain along the left lower limb as well as common peroneal nerve neuropathy of 18 months' duration. After open excision of the fabella, this patient had a significant improvement at 3 months with full recovery at 1 year.…”
mentioning
confidence: 99%